2020
DOI: 10.1155/2020/7649157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biomechanical Properties of the Lumbar Extensor Myofascia in Elderly Patients with Chronic Low Back Pain and That in Healthy People

Abstract: There is limited research on the changes of biomechanical characteristics of the lumbar extensor myofascia in elderly patients with chronic low back pain. This study aimed to compare the biomechanical properties of the lumbar extensor myofascia in elderly patients with chronic low back pain and healthy people when resting and to analyze the relationship between the Japanese Orthopedic Association (JOA) score, visual analog scale (VAS) score, Cobb angle, and disease course and the biomechanical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
(74 reference statements)
7
20
0
Order By: Relevance
“…Therefore, cervical decrement, that is inverse to the elasticity, seems to be the main mechanical property that discriminates groups. Recently, it has been reported that elasticity is lower in elderly patients with chronic LBP [ 44 ] and in patients with ankylosing spondylitis [ 45 ], although always when assessed in lumbar region, which is consistent with the current results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, cervical decrement, that is inverse to the elasticity, seems to be the main mechanical property that discriminates groups. Recently, it has been reported that elasticity is lower in elderly patients with chronic LBP [ 44 ] and in patients with ankylosing spondylitis [ 45 ], although always when assessed in lumbar region, which is consistent with the current results.…”
Section: Discussionsupporting
confidence: 92%
“…The mean values of lumbar musculature stiffness of young control subjects [ 28 ] and elder control subjects [ 44 ] were similar to those values obtained in the current study for all groups. Furthermore, current values of tone and stiffness were lower than those reported for other pathological populations, such as young [ 28 , 71 ] and elderly [ 44 ] individuals with chronic spinal pain, and even inflammatory pain [ 29 ]. In fact, the differences among the three groups, which did not show statistical significance, were lower than the minimum detectable change established for these variables in the lumbar muscles [ 29 ], and may be explained by the acute state of patients in our study, and the rest assessment position.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…38,39 A myotonometer measures the resistance of a tissue to an impulse force applied to the overlying skin and quantifies stiffness based on the damped natural oscillation response of the tissue. 40,41 This technique is reliable in measuring stiffness of the lumbar erector spinae in back-healthy controls 38 and has identified greater lumbar erector spinae stiffness in females with LBP compared with controls 41 and older patients with LBP, 42 as well as greater lumbar myofascial stiffness in patients with ankylosing spondylitis compared with age-comparable controls. 43 Myotonometry is unable to determine joint stiffness; however, when used in conjunction with the previously described passive jig, it may provide powerful insight into how tissues of the low back contribute to the lumped mechanical stiffness measure.…”
mentioning
confidence: 99%